Lung cancer screening in the elderly. (June 2013) - Jaklitsch, Michael T; Armstrong, Katherine; Jacobson, Francine L
The National Lung Screening Trial found a 20% decrease in lung cancer-specific mortality using low-dose computed tomography to screen individuals with a 30 pack-year history of smoking, aged 55–75 years. Increasing age is an independent risk factor for lung cancer. Thus, elderly patients stand to benefit the most from low-dose computed tomography screening. Based upon the peak age of lung cancer diagnosis, currently 71 years, screening until at least the age of 79 years will continue to provide benefit to the healthy elderly who have largely outlived their birth cohort. Consideration for low-dose computed tomography in older elderly individuals should be based upon functional status and reserve on a case-by-case basis. These adaptations are contained within the 2012 American Association for Thoracic Surgery Lung Cancer Screening Guidelines.